Review of Research on Regenerative Braking Control Strategy of New Energy Vehicle - Fei Xie; Yongfa Qin (Jixie chuandong)
Aiming at the regenerative braking control problem of new energy vehicles， four basic regenerative braking control strategies， fuzzy control strategies， neural network control strategies， and the research status of comprehensive optimization control strategies based on the above control strategies are summarized. The hot issues of various control strategies in the stage of theoretical exploration are summarized. The analysis shows that the research on regenerative braking control strategy based on fuzzy control theory and integrating multiple intelligent algorithms has a good research prospect and engineering application potential.